Evaluation of mathematics learning a brief study on memorization of formulas in learning verification - José Pereira, André; Figueredo Monção, Fabrício; Oliveira Vieira, Savio; Almeida Antunes, Geancarlo; Cantuária Ribeiro, Flávio (Seven Editora, 2023)
In this work, we present a discussion on the subject that is frequently questioned in the classroom: "Providing pre-established expressions in the evaluation" that "simplify" the reasoning process at the time of calculation and interpretation, which are known as mathematical formulas. The objective is to understand what are the positive and negative points of this evaluation methodology. The research was based on a questionnaire applied to mathematics teachers who work at different levels of basic and higher education. An evaluation was also applied in a class of school X in the city of Janaúba-MG to verify the performance of the students using the two methodologies discussed. The results show that the formulas do not matter if the student does not know how to use them, but it is a facilitators in the studies. However, some challenges in the student’s life require him to "know" the pre-defined formula, such as entrance exams.